2022
DOI: 10.1039/d2dt01707e
|View full text |Cite
|
Sign up to set email alerts
|

Versatile chemistry of six-membered NHC with boranes: bromination at sp3 borane, activation of the B–H bond of HBpin, and ring expansion of NHC

Abstract: The NHC•borane chemistry has been majorly restricted to imidazol-2-ylidene classes of carbenes. In our previous communication, we have reported the synthesis of 6-SIDipp•BH3 [6-SIDipp = 1,3-di(2,6-diisopropylphenyl) tetrahydropyrimidine-2-ylidene] and its electrophilic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 47 publications
5
18
0
Order By: Relevance
“…During the submission of our work, Mukherjee and coworkers reported the formation of a Zn(II) hydride species from fluorenyl‐tethered NHC⋅ZnBrN(TMS) 2 complex upon reaction with HBpin, and the resultant zinc hydride species has been employed as a catalyst for the regioselective hydroboration of N‐heteroarenes [20] . In the same vein, we have also reacted 1 with pinacolborane (HBpin) to prepare the zinc hydride, however, the reaction led to the extrusion of ZnEt 2 and 6‐SIDipp mediated B−H activation of HBpin took place, which was recently reported by our group [14] . We speculate that zinc complexes of 6‐SIDipp are prone to dissociation, which was also noted by Hilmyer and Tollman [4b] …”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…During the submission of our work, Mukherjee and coworkers reported the formation of a Zn(II) hydride species from fluorenyl‐tethered NHC⋅ZnBrN(TMS) 2 complex upon reaction with HBpin, and the resultant zinc hydride species has been employed as a catalyst for the regioselective hydroboration of N‐heteroarenes [20] . In the same vein, we have also reacted 1 with pinacolborane (HBpin) to prepare the zinc hydride, however, the reaction led to the extrusion of ZnEt 2 and 6‐SIDipp mediated B−H activation of HBpin took place, which was recently reported by our group [14] . We speculate that zinc complexes of 6‐SIDipp are prone to dissociation, which was also noted by Hilmyer and Tollman [4b] …”
Section: Resultsmentioning
confidence: 63%
“…Due to our recent success in the chemistry of six‐membered saturated NHCs [12–15] and to expand the family of 6‐NHC⋅Zn complexes, in the present work we report on the synthesis and characterization of several novel zinc complexes coordinated to saturated 6‐SIDipp ligand (6‐SIDipp=1,3‐di(2,6‐diisopropylphenyl) tetrahydropyrimidine‐2‐ylidene). Unlike 5‐NHCs all the complexes are monomeric in nature, reflecting the greater σ‐donation of 6‐NHC than the formers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated substitution reactions of 6-SIDipp•BH 3 , ring expansion with 6-SIDipp•9BBN, and activation of the B-H bond of HBpin with 6-SIDipp. [17][18][19] These studies have…”
Section: Introductionmentioning
confidence: 97%
“…We demonstrated substitution reactions of 6-SIDipp$BH 3 , ring expansion with 6-SIDipp$9BBN, and activation of the B-H bond of HBpin with 6-SIDipp. [17][18][19] These studies have indicated that 6-SNHC has a notably higher donating capacity than 5-NHC. Our hypothesis was that by incorporating the 6-SNHC framework, along with bulky Dipp groups, and using a Lewis acid, we could potentially achieve the isolation of a single, parent oxoborane molecule.…”
Section: Introductionmentioning
confidence: 99%